The development of hydraulic oils for the new fuel-efficient hydraulic hybrid vehicles with ANP method. Issue 3 (9th April 2018) - Tang, Gongbin; Chen, Yifan; Xiao, Feng; Zhang, Shanshan; Huang, Fuchuan
Abstract : Purpose: This paper aims to use this method to explore a new approach and possible technical optimal design for lubricant formulation. Design/methodology/approach: The component of the developed oil was determined based on the physical and chemical properties of the base oil and the tribological properties. The analytic hierarchy process (ANP) method and SuperDecisions software were used for hydraulic oil modeling and calculation while taking performance index, work circumstance and economy into consideration. Findings: The hydraulic oil formulation can be optimized using the ANP method, where the technical performance, economy and working circumstances of the hydraulic oils were taken into consideration in the evaluation system. The experiment analyzed and scored and screened the hydraulic oil formula in an objective and comprehensive manner. Originality/value: The experiments showed that the newly developed hydraulic oils could meet the performance requirements for new energy vehicles equipped with hybrid hydraulic engines.